Translation, adaptation and pilot testing of the Pictorial Fit-Frail Scale (PFFS) for use in Malaysia – The PFFS-Malay version (PFFS-M) - Sally, Ahip; Sazlina, Shariff Ghazali; Sabrina, Lukas; Azah, Abdul Samad; Ummu Kalsum, Mustapha; Olga, Theou; Renuka, Visvanathan (ACADEMY OF FAMILY PHYSICIANS OF MALAYSIA, 2021)
Background: Frailty is an important health issue in an aging population; it is a state of vulnerability that renders the elderly susceptible to adverse health outcomes, including disability, hospitalization, long-term care admission and death. Early frailty stages are recognizable through screening and are reversible with targeted interventions. To date, however, there is no screening tool for use in Malaysia. The English Pictorial Fit-Frail Scale (PFFS) is a visual tool that assesses a person’s fitness-frailty level in 14 health domains, with higher scores indicating higher frailty. Objective: The aim was to translate and adapt the English PFFS for use in Malaysian clinical settings. Methods: The original English PFFS underwent forward and backward-translation by two bilingual translators to and from the Malay language. A finalized version, the PFFS-Malay (PFFS-M), was formed after expert reviewers’ consensus and was pilot tested with 20 patients, 20 caregivers, 16 healthcare assistants, 17 nurses and 22 doctors. Score agreement between patients and their caregivers and among healthcare professionals were assessed. All participants rated their understanding of the scale using the feasibility survey forms. Results: A total of 95 participants were included. There were high percentages of scoring agreements among all participants on the scale (66.7% to 98.9%). Overall feedback from all respondents were positive and supported the face validity of the PFFS-M. Conclusion: The PFFS-M reflects an accurate translation for the Malaysian population. The scale is usable and feasible and has face validity. Reliability and predictive validity assessments of the PFFS-M are currently underway.